Vulva carcinoma. Study of 14 cases with special emphasis on the radical surgical treatment - Valdivia P., Eduardo (2015)
From June 1, 1952 to May 31, 1956. we have seen 14 cases of cancer of the vulva at the Instituto Nacional de Enfermedades Neoplásicas. This represent a 0.82% of the all the malignancies of lhe genital tract (1691 cases). This percentages is lower than reported by other authors, This, however, is relativo, because we have a high frequency of carcinoma of the cervix. AII these patients were of the past menopausal age. The youngest was 58 an the oldest 85 years. The greatest numbers of cases were between the ages of 60 and 70 years, as Taussig found. In 71% of these patients we found pre-cancerous lesions such as leukoplakia and pruritus. The time interval between this lesion and the appearance of malignancy varied from months to years. The clinical diagnosis was corroborated by the biopsy, with the exception of one case, in wich the clinical diagnosis was Hidradenoma and the pathological report was carcinoma. Histologically, all the cases were epidermoid carcinoma. The frequency of ganglionar metastasis we could not detect clinically but the malignancy proven by the pathological studies, shows that radical surgical treatment is the best. The last 4 cases that we saw we treated with radical surgery, following the Stanley Way technique, with satisfactory results. Enough time has not elapsed for us to speak of cure, but until now there has been no recurrence of malignancy.